Protocol for a multicentre randomised feasibility trial evaluating early Surgery Alone In LOw Rectal cancer (SAILOR). Issue 11 (21st November 2016) - Harris, Dean A; Thorne, Kymberley; Hutchings, Hayley; Islam, Saiful; Holland, Gail; Hatcher, Olivia; Gwynne, Sarah; Jenkins, Ian; Coyne, Peter; Duff, Michael; Feldman, Melanie; Winter, Des C; et al.
Abstract : Introduction: There are 11 500 rectal cancers diagnosed annually in the UK. Although surgery remains the primary treatment, there is evidence that preoperative radiotherapy (RT) improves local recurrence rates. High-quality surgery in rectal cancer is equally important in minimising local recurrence. Advances in MRI-guided prediction of resection margin status and improvements in abdominoperineal excision of the rectum (APER) technique supports a reassessment of the contribution of preoperative RT. A more selective approach to RT may be appropriate given the associated toxicity. Methods and analysis: This trial will explore the feasibility of a definitive trial evaluating the omission of RT in resectable low rectal cancer requiring APER. It will test the feasibility of randomising patients to (1) standard care (neoadjuvant long course RT±chemotherapy and APER, or (2) APER surgery alone for cT2/T3ab N0/1 low rectal cancer with clear predicted resection margins on MRI. RT schedule will be 45 Gy over 5 weeks as current standard, with restaging and surgery after 8–12 weeks. Recruitment will be for 24 months with a minimum 12-month follow-up. Objectives: Objectives include testing the ability to recruit, consent and retain patients, to quantify the number of patients eligible for a definitive trial and to test feasibility of outcomes measures. These include locoregional recurrence rates, distance to circumferential resection margin, toxicity and surgical complications including perineal wound healing, quality of life and economic analysis. The quality of MRI staging, RT delivery and surgical specimen quality will be closely monitored. Ethics and dissemination: The trial is approved by the Regional Ethics Committee and Health Research Authority (HRA) or equivalent. Written informed consent will be obtained. Serious adverse events will be reported to Swansea Trials Unit (STU), the ethics committee and trial sites. Trial results will be submitted for peer review publication and to trial participants. Trial registration number: ISRCTN02406823.